Sustainable development goals : harnessing business to achieve the SDGs through finance, technology and law reform - Walker, Julia; Pekmezovic, Alma; Walker, Gordon (Gordon R.) (Chichester, West Sussex, United Kingdom : Wiley, 2019)
Achieving the Sustainable Development Goals through Finance, Technology and Law Reform Achieving the SDGs requires a fundamental rethink from businesses and governments across the globe. To make the ambitious goals a reality, trillions of dollars need to be harnessed to mobilise finance and accelerate progress towards the SDGs. Bringing together leaders from the World Bank, the financial and business sectors, the startup community and academia, this important, topically relevant volume explains what the SDGs are, how they came about and how they can be accelerated. Real-world case studies and authoritative insights address how to direct investment of existing financial resources and re-align the global financial system to reflect the SDGs. In depth chapters discuss how financial institutions, such as UBS Wealth Management, Manulife Asset Management and Moody's Rating Agency are supporting the SDGs. The opportunities arising from Blockchain, Big Data, Digital Identity and cutting-edge FinTech and RegTech applications are explored, whilst the relevance of sustainable and transparent global supply chains is underscored. Significant attention is paid to law reform which can accelerate progress of the SDGs through SME Financing, Crowdfunding, Peer-to-Peer Lending and tax restructuring. To achieve the'World We Want', much needs to be done. The recommendations contained within this book are critical for supporting a fundamental shift in thinking from business and governments around the world, and for building a more just and prosperous future for all.
About the Editors Notes on Contributors Foreword Mahmoud Mohieldin Foreword: Why we need to accelerate implementation of the SDGs. Rt. Hon. Helen Clark Preface Introduction Part One Overview and Context Chapter 1 The UN and Goal Setting: From the MDGs to the SDGs Alma Pekmezovic Chapter 2 SDGs and the Role of International Financial Institutions Suresh Nanwani Chapter 3 Towards a New Global Narrative for the Sustainable Development Goals? Iason Gabriel and Varun Gauri Chapter 4 Overcoming Scarcity -- the Paradox of Abundance: Harnessing Digitalisation in Financing Sustainable Development Simon Zadek Part Two Where will the money come from? Financing the SDGs Chapter 5 The New Framework for Financing the 2030 Agenda for Sustainable Development and the SDGs Alma Pekmezovic Chapter 6 The Contribution of the International Private Sector to a more Sustainable Future Martin Blessing and Tom Naratil Chapter 7 Re-Orienting the Global Financial System Towards Sustainability Alma Pekmezovic Chapter 8 How Asset Managers can Better Align Public Markets Investing with the SDGs Emily Chew and Margaret Childe Chapter 9 The Significance of Sustainable Development Goals for Government Credit Quality Alastair Wilson Part Three Technology, Innovation and Entrepreneurship Chapter 10 FinTech for Financial Inclusion: Driving Sustainable Growth Dirk A. Zetzsche, Ross P. Buckley & Douglas W. Arner Chapter 11 Financing and Self-Financing of SDGs through Financial Technology, Legal and Fiscal Tools Jon Truby Chapter 12 SDG Challenges In G20 Countries Guillaume Lafortune and Guido Schmidt-Traub Chapter 13 The Future-Fit Business Benchmark: Flourishing Business in a Truly Sustainable Future Geoff Kendall and Martin Rich Chapter 14 Financing for Youth Entrepreneurship in Sustainable Development Inna Amesheva, Alex Clark, Julian Payne Chapter 15 Digitisation in the Supply Chain Julia Walker Part Four Facilitating the SDGs by Legal Infrastructure Reform Chapter 16 Facilitating Sustainable Development Goal 8 by Legal Reform Measures Gordon Walker Chapter 17 Facilitating SDGs by Tax System Reform Benjamin Walker Chapter 18 Facilitating SDGs by Competition and Consumer Law and Policy Reform: Aspirations and Challenges in PNG Brent Fisse Appendix: Transforming our world: the 2030 Agenda for Sustainable Development UN General Assembly Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on September 09, 2019).
Keywords: Sustainable Development Goals; Sustainable development -- International cooperation; Economic development -- Developing countries; Poverty -- Developing countries; Electronic books